Phenomenon of Cultural, Political and Educational Corruption in Colombia - Quintero-Calvache, Juan-Carlos; Rengifo-Carpintero, John-Alexis (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The investigation is a denunciation of the way in which in Colombia since the 80's it has produced an imaginary institution: a corrupt, delinquent culture and aesthetic narco as a socially legitimized way of life. To do this, the social dimensions that fertilize it will be revealed: first, the neighborhood cultural imagination of the self is alive born of the way of life instituted by drug trafficking emerged from the world of Antioquia life. Second, dishonest criminal practices within the capitalist enterprise and the state bureaucracy; Thirdly, university culture, especially the academic imaginary of private institutions at all, has a price to achieve success. The methodology is critical phenomenological: how it is discovered how the Colombian citizen has been permeated in his social, and individual, imaginary by the mafia culture, reproducing culturally criminal worlds of life. It is concluded that Colombia produces an imaginary anti-cultural paradigm. A society that boasts of its pathology: corruption as a mechanism of action and social legitimation.